Role of microRNA in the risk stratification of ischemic strokes - Hosam M. Al-Jehani; Hosam M. Al-Jehani; Hosam M. Al-Jehani; Hosam M. Al-Jehani; Ahmed Hafez Mousa; Ahmed Hafez Mousa; Ahmed Hafez Mousa; Ahmed Hafez Mousa; May Adel Alhamid; Fawaz Al-Mufti (Frontiers in Neurology)
BackgroundIschemic stroke is a major cause of death and morbidity, and risk classification is essential for predicting therapeutic outcomes. MicroRNAs may be useful indicators for risk stratification, as they control gene expression and influence physiological and pathological processes.MethodologyA systematic strategy was developed to search relevant material using databases like PubMed, Scopus, and Web of Science. Selection criteria included human research, a certain date, or categories of studies. Data extraction, synthesis, and analysis were carried out to find trends, similarities, and differences among the chosen studies. The study’s design, sample size, methodology, statistical analysis, and any potential biases or restrictions from the selected reference papers were also taken into account.Results and findingsMicroRNA is an important biomarker for risk stratification in Ischemic Strokes. It can be used to identify Stroke-Specific microRNA Signatures, identify diagnostic and prognostic values, and regulate Vascular Inflammation, Endothelial Dysfunction, and Thrombus Formation and Resolution. It also has potential therapeutic applications.ConclusionMicroRNAs have emerged as promising biomarkers for predicting stroke risk, severity of strokes, and clinical outcomes. They can be used to predict the severity of a stroke and aid clinicians in making treatment decisions.